Spatial and Temporal Distribution of Outdoor Particulate Matter (PM2.5) Levels for Locations within Two Local Government Areas in Edo State, Southern Nigeria - Obayagbona, Nosa; Omorede, Odigie (Indonesian Journal of Social and Environmental Issues (IJSEI), 2025)
Particulate matter (PM) are airborne microscopic sized particles of solid or liquid matter. This study investigated the spatial distribution of PM2.5 concentrations and assessed PM2.5 related air quality in both Egor and Oredo Local Government Areas (LGAs) of Edo State. Twenty outdoor locations were monitored once monthly from June to July 2023 using BiaolingTM air quality monitor. The values obtained were subjected to unpaired t test analyses which were conducted at 95% probability level. For sampled areas in Oredo LGA, mean PM2.5 values ranged from 10.3 μg/m3 ± 0.1 to 45.3 μg/m3 ± 0.2 whilst a range of PM2.5 values; 12 μg/m3 ± 0.2 to 42 μg/m3 ± 0.1 was recorded for locations in Egor LGA. Statistical analysis revealed an insignificant difference in PM2.5 mean data between the two months (p > 0.05) in both LGAs. There was an insignificant difference between the PM2.5 for June and July, 2023 in both LGAs (p>0.05). The drawn spatial maps for both LGAs revealed that the PM2.5 related air quality index (AQI) values was good in majority of the sampled areas with the exception of New Benin in Oredo LGA and Orovbie sampling point in Egor LGA.  More studies should be conducted with  focus on the evaluation of outdoor air quality in more areas within these LGAs as well as well likely and implementable cost effective abatement measures that can lower the magnitude of PM pollution in the respective study areas.